Associations Between Inflammatory Adipokines, Liver Steatosis, and Fibrosis in Patients with Different Degrees of Adiposity with or Without Metabolic Syndrome - Lopes, Karynne Grutter; Souza, Maria das Graças Coelho de; Lopes, Fernanda de Azevedo Marques; da Silva Junior, Vicente Lopes; Terra, Carlos Antonio; Carvalho, Ana Teresa Pugas; Bouskela, Eliete; Kraemer-Aguiar, Luiz Guilherme (Hormone and Metabolic Research, 2025)
The aim of this cross-sectional study was to compare and test associations between inflammatory profiles and liver steatosis/fibrosis in individuals with different degrees of adiposity with or without metabolic syndrome. Forty-six patients (82.6% females, aged 38.3±7.8 yr, body mass index of 32.6±5.1 kg/m2) were allocated into three groups according to body adiposity and the presence or absence of metabolic syndrome: normal-weight controls, patients with obesity or with obesity and metabolic syndrome. Between-group comparisons were performed for clinical history, anthropometry, biochemical, metabolic, and inflammatory profiles, and degree of liver stiffness and steatosis by transient elastography. As expected, obesity and obesity and metabolic syndrome had greater body mass index and waist circumference than controls. No significant differences between groups in lipid profile, aspartate aminotransferase, ferritin, adiponectin, and retinol-binding protein-4 were noted. Obesity and metabolic syndrome had significantly higher fasting glucose levels compared to controls and obesity. A more significant proportion of patients with hypertension, higher insulinemia, HOMA-IR, glycated hemoglobin, aspartate aminotransferase, gamma-glutamyltransferase, tumor necrosis factor-alpha, interleukin-6, and leptin were observed in obesity and metabolic syndrome compared to controls. Obesity had higher alkaline phosphatase, interleukin-6, and leptin levels than controls. Liver stiffness and steatosis were higher in obesity and metabolic syndrome than in controls, while hepatic fibrosis degree F2 occurred more frequently in obesity and metabolic syndrome (p≤0.03). No associations were detected between liver stiffness and steatosis and inflammatory biomarkers in the studied groups (p≥0.07). Our findings highlight the impact of metabolic conditions on liver health but also suggest that systemic inflammation might not be directly linked to liver stiffness and steatosis.
Keywords: metabolic syndrome; obesity; inflammation; metabolic dysfunction-associated fatty liver disease